Jugoslovanski jedrski program v kontekstu hladne vojne (1948–1971) - Korolija, Maja (Filozofski vestnik, 2025)
Following the end of the Second World War, Yugoslavia embraced the Soviet ideological conception of society as the ideal model for all spheres of life, including science. In accor-dance with this, scientific work in the country should be planned, centralized and defined by the party-line. After the break-up with the USSR in 1948, especially at first, Yugoslavia showed a strong geopolitical inclination toward the Western Bloc. This led to the formati-on of a new state system of “Socialist Self-Management,” but also brought about the rise of new discursive and organizational trends in Yugoslav science, which were compatible with certain elements of the perspective of science as autonomous – the hegemonic idea of science in the West. We will present the development of the Yugoslav nuclear program in the period from 1948 to 1971. Despite changes that occurred due to the geopolitical shift in the domain of scientific organization and scientific discourse in Yugoslav science, we’ll show that the established organization of the nuclear program was much more in line with the Soviet model. Only when the nuclear program began to lose its political impor-tance was it directed towards greater autonomy, which implied a greater focus on invest-ment efficiency, i.e. limiting state investments and control. Our aim is to analyse the func-tion of two dominant Cold War perspectives on science in the context of geopolitical and socio-economic processes of the (semi)peripheral Yugoslav socialist system, their mani-fest and latent functions on the example of the nuclear program.
Keywords: Cold War; hladna vojna; ideologija; ideology; jedrsko orožje; nuclear weapon; science; znanost